2008
DOI: 10.1007/s00894-008-0287-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a complete cycle of acetylcholinesterase catalysis by ab initio QM/MM modeling

Abstract: The reaction mechanism of acetylcholine hydrolysis by acetylcholinesterase, including both acylation and deacylation stages from the enzyme-substrate (ES) to the enzyme-product (EP) molecular complexes, is examined by using an ab initio type quantum mechanical - molecular mechanical (QM/MM) approach. The density functional theory PBE0/aug-6-31+G* method for a fairly large quantum part trapped inside the native protein environment, and the AMBER force field parameters in the molecular mechanical part are employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 39 publications
5
34
2
Order By: Relevance
“…Therefore, due to the stabilizing effect of Glu325 on the imidazolium cation, the one proton mechanism is ener getically more favorable. These results are in complete agreement with the results of our previous calculations of the hydrolysis in the active site of acetylcholinesterase, which is similar in the structure and the mechanism of hydrolysis to BuChE, 13 and also with other results of mod eling of the mechanisms of hydrolysis of serine proteases 28 and carboxypeptidases. 10 To sum up, the results of QM/MM simulation showed that the Asp70Gly single mutation of butyrylcholinest erase does not lead to the qualitatively different energy profile of the hydrolysis of succinylcholine for the acyla tion step compared to the native enzyme.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, due to the stabilizing effect of Glu325 on the imidazolium cation, the one proton mechanism is ener getically more favorable. These results are in complete agreement with the results of our previous calculations of the hydrolysis in the active site of acetylcholinesterase, which is similar in the structure and the mechanism of hydrolysis to BuChE, 13 and also with other results of mod eling of the mechanisms of hydrolysis of serine proteases 28 and carboxypeptidases. 10 To sum up, the results of QM/MM simulation showed that the Asp70Gly single mutation of butyrylcholinest erase does not lead to the qualitatively different energy profile of the hydrolysis of succinylcholine for the acyla tion step compared to the native enzyme.…”
Section: Resultssupporting
confidence: 93%
“…40 However, a series of recent studies demonstrated that at a low substrate concentration, hydrolysis of ACh is rate-determined by the acylation reaction, 2, 41, 46 which is consistent with our recently reported study. 47 Despite extensive studies on the catalytic mechanisms of cholinesterase-catalyzed hydrolysis of ACh/ATCh, 1-2, 15, 27-30, 33-34, 36, 38, 48-50 questions remain for the mechanism of the substrate activation for BChE-catalyzed hydrolysis of ACh/ATCh. For example, what is the main factor leading to the observed substrate activation effect?…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Several molecular modelling studies available in literature point out to important features on the oximes structures that could be very useful to guide experimental research on this issue. [7][8][9][10][11][12][13][14][15][16][17][18][19] In a former work 4 …”
Section: Introductionmentioning
confidence: 99%